Regioselective formation of six-membered platinacycles by C–X and C–H oxidative addition. Issue 46 (18th November 2015) - Anderson, Craig M.; Greenberg, Matthew W.; Balema, Tedros A.; Duman, Leila M.; Oh, Nathaniel; Hashmi, Asad; Ladner, Leah; Jain, Kyan; Yu, David; Tanski, Joseph M.
Graphical abstract: Appropriately designed ligands allow for regioselective formation of six-membered platinacycles. Abstract: Several naphthyl-based N^N^C ligands were synthesized by strategically incorporating a bromide or iodide at the 8-position of the naphthyl ring. When allowed to react with the platinum tetra methyl dimer, PtMe4 (μ-SMe2 )2, the more rare six-membered platinum(IV) platinacycles were formed by oxidative addition of the C(sp 2 )–X bond. In a separate case, C–H activation at the 8-position was encouraged by having the 2-position 'blocked' with a methyl group thus a six-membered platinum(II) platinacycle was formed by C(sp 2 )–H activation at the 8-position. Products were characterized by XRD, NMR, UV/vis, emission spectroscopy, and HRMS. The platinum(IV) compounds were inert to thermolysis. The complexes appear to exhibit dual fluorescence and phosphorescence at room temperature in solution.